Selenium Promotes T-Cell Response to TCR-Stimulation and ConA, but Not PHA in Primary Porcine Splenocytes - Ren, Fei; Chen, Xingxiang; Hesketh, John; Gan, Fang; Huang, Kehe (PLOS ONE, 2012)
There is controversy in the literature over whether the selenium (Se) influences cellular immune responses, and the mechanisms possibly underlying these effects are unclear. In this study, the effects of Se on T-cell proliferation and IL-2 production were studied in primary porcine splenocytes. Splenocytes were treated with different mitogens in the presence of 0.5–4 µmol/L sodium selenite. Se significantly promoted T-cell receptor (TCR) or concanavalin A (ConA)-induced T-cell proliferation and IL-2 production but failed to regulate T-cell response to phytohemagglutinin (PHA). In addition, Se significantly increased the levels of cytosolic glutathione peroxidase (GPx1) and thioredoxin reductase 1 (TR1) mRNA, the activity of GPx1 and the concentration of reduced glutathione (GSH) in the unstimulated, or activated splenocytes. These results indicated that Se improved the redox status in all splenocytes, including unstimulated, TCR, ConA and PHA -stimulated, but only TCR and ConA-induced T-cell activation was affected by the redox status. N-acetylcysteine (NAC), a pharmacological antioxidant, increased T-cell proliferation and IL-2 production by TCR and ConA stimulated splenocytes but had no effect on the response to PHA in primary porcine splenocytes confirming that PHA-induced T-cell activation is insensitive to the redox status. We conclude that Se promotes GPx1 and TR1 expression and increases antioxidative capacity in porcine splenocytes, which enhances TCR or ConA -induced T-cell activation but not PHA-induced T-cell activation. The different susceptibilities to Se between the TCR, ConA and PHA -induced T-cell activation may help to explain the controversy in the literature over whether or not Se boosts immune responses.